Kinetics of Cr(III) and Cr(VI) removal from water by two floating macrophytes - Maine, Maria Alejandra (2016)
The aim of this work was to compare Cr(III) and Cr(VI) removal kinetics from water by Pistia stratiotes and Salvinia herzogii. The accumulation in plant tissues and the effects of both Cr forms on plant growth were also evaluated. Plants were exposed to 2 and 6 mg L−1 of Cr(III) or Cr(VI) during 30 days. At the end of the experiment, Cr(VI) removal percentages were significantly lower than those obtained for Cr(III) for both macrophytes. Cr(III) removal kinetics involved a fast and a slow component. The fast component was primarily responsible for Cr(III) removal while Cr(VI) removal kinetics involved only a slow process. Cr accumulated principally in the roots. In the Cr(VI) treatments a higher translocation from roots to aerial parts than in Cr(III) treatments was observed. Both macrophytes demonstrated a high ability to remove Cr(III) but not Cr(VI). Cr(III) inhibited the growth at the highest studied concentration of both macrophytes while Cr(VI) caused senescence. These results have important implications in the use of constructed wetlands for secondary industrial wastewater treatment. Common primary treatments of effluents containing Cr(VI) consists in its reduction to Cr(III). Cr(III) concentrations in these effluents are normally below the highest studied concentrations in this work.